Antlions in the Classroom - S. McCann; J.D. Ellis; M.K. O Malley (EDIS)
This document is designed to be used with other entomology youth curricula and is suitable for any age group. It details the process of using antlions for live insect illustrations in the classroom. Antlions, belonging to the Order Neuroptera, create conical depressions to trap prey. The document covers finding, capturing, and keeping antlions, feeding them, and observing their life cycle. It also provides suggestions for classroom lessons and activities involving antlions, emphasizing their accessibility and educational value. First published: January 2008.